Zofia Berdychowska, Heinz-Helmut Lüger, Czesława Schatte, Grażyna Zenderowska- -Korpus (Hrsg.). Phraseologie als Schnittstelle von Sprache und Kultur II. Öffentlicher Raum – Medien – Phraseodidaktik. Frankfurt am Main: Peter Lang 2017, S. 221 - Woźniak, Joanna (Glottodidactica, 2019)
.